Synthesis of new simple hole-transport materials bearing benzodithiazole based core for perovskite solar cells - Swetha T.; Karim M.R.; Alharbi H.F.; Alharthi N.H.; Bais B.; Amin N.; Akhtaruzzaman M. (Elsevier Ltd, 2023)
Cost effectiveness; Cyclic voltammetry; Mass spectrometry; Organic compounds; Perovskite; 5]thiadiazole; Hole transport materials; Mass spectroscopy; Optical parameter; Organic hole transport materials; Photophysical properties; Synthetic routes; Theoretical study; Perovskite solar cells; aromatic hydrocarbon; fluorine; perovskite; photochemistry; photovoltaic system; purification; transportation